The Effectiveness of the Discussion Method to Increase Students' Understanding and Activeness in Islamic Religious Education Subjects - Yusi Tasika; Giyarsi (PT. Islamic Research Publisher, 2022)
This study aims to determine whether the discussion method is effective in increasing students' understanding and activeness in PAI learning at SMP Negeri 39 Bengkulu Utara by looking at the learning outcomes and the results of the students' answers to questionnaires. The type of research used is a quantitative research method using a quasi-experimental design (quasi-experimental). Data collection techniques that researchers use are observation, tests, questionnaires and documentation. And data analysis was carried out with normality test and homogeneity test, as well as hypothesis testing. The results of the research conducted by researchers can be concluded that: 1) The discussion method is effective for improving students' understanding in PAI learning, judging from the comparison of the final grade results from the class using the discussion method (experimental) with the class using conventional methods as evidenced by the t-value of 4,467. and the significance level of p = 0.000. These results show p < 0.05, meaning it can be taken a decision that there are differences in students' understanding in PAI learning using the discussion method with the conventional method the average value of the final test (post-test) learning outcomes using the discussion method are higher than the results of the final test using the discussion method. conventional method. This means that there is a significant increase in learning outcomes to measure students' understanding of PAI learning. 2) The discussion method is effective to increase student activity in PAI learning. This is evidenced by the obtained t value of -2.154 and a significance level of p = 0.036. These results show p < 0.05, meaning that a decision can be made that there is a significant difference in student activity in PAI learning using the discussion method with the conventional method.